Identificação estrutural de metabólitos provenientes do metabolismo in vitro de compostos bioativos e estudos de fenotipagem enzimática - Cardoso, Josiane de Oliveira (2015)
This work reports studies of in vitro metabolism involving the compound 3-(2-chloro-6-fluorobenzyl)- imidazolidine-2,4-dione (LPSF-PT-31), a new 2-adrenoceptor agonist and, studies of enzyme phenotyping of montelukast, a drug used for the treatment of asthma. The results of this study revealed that LPSF-PT-31 is metabolized via CYP P450s in rat and human liver microsomes, producing only one major hydroxy-metabolite. LPSFPT- 31 showed a higher rate of in vitro metabolism in rats, which suggests a greater exposure to the drug in humans. The structural identification of LPSF-PT-31 metabolite’s was achieved through LC-MSn and 1H-NMR analysis that provided data to conclude that the hydroxylation occurred in the 5th position of the imidazolidine ring yielding to the production of 3-(2-chloro-6-fluorobenzyl)-5-hydroxyimidazolidine-2,4- dione. Related to the studies of enzyme phenotyping of montelukast, it was observed that the glucuronidation is the main clearance pathway of montelukast accounting for ~85% of the total apparent in vitro Clint (CYPs +UGTs) and that the CYP-mediated oxidation accounts only for ~15% to the overall metabolism of the drug, being montelukast acyl-β-D-glucuronide and montelukast 1,2 diol the major metabolites formed via UGTs and CYPs, respectively. Kinetic studies, correlation analysis, inhibition studies and, experiments in expressed CYPs and UGTs revealed that the CYP2C9 and CYP2C8 are comparably involved in the formation of montelukast 1,2- diol. CYP3A4 was responsible for the formation of 21(R)-OH montelukast and 21(S)- OH montelukast, while multiple CYPs catalyzed the formation of 25-OH montelukast (CYP2C8>2C9>3A4>2C19). The direct glucuronidation of montelukast resulted in the formation of montelukast acyl-β-D-glucuronide and of a new metabolite (Mglucuronide) not reported previously and was exclusively catalyzed by isoform UGT1A3. In conclusion, the in vitro data suggest that the applicability of montelukast as a probe of CYP2C8 activity in vitro and in vivo may be severely compromised due to important role of UGT1A3 and involvement of multiple CYPs in its metabolism. In addition, considering the lack of selective markers for UGT1A3, montelukast may be used as a selective marker of the UGT1A3 in vitro and in vivo.